Feasibility of a co-designed and personalised intervention to improve vegetable intake in rural-dwelling young adults - Katherine Mary Livingstone; Jonathan C. Rawstorn; Stephanie R. Partridge; Yuxin Zhang; Eric O; Stephanie L. Godrich; Sarah A. McNaughton; Gilly A. Hendrie; Kathleen M. Dullaghan; Gavin Abbott; Lauren C. Blekkenhorst; Ralph Maddison; et al. (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background This study determined the feasibility, acceptability, engagement and efficacy of a co-designed and personalised digital intervention to increase vegetable intake (Veg4Me) in young (18-to-35 years) rural-dwelling Australian adults. Methods Participants living in rural Australia were recruited via local government networks and social media and randomised to receive 12-weeks’ access to personalised (intervention) or non-personalised (control) versions of the free Veg4Me web application. The intervention included: (1) personalised recipes, (2) geo-located food environment map, (3) healthy eating resources, (4) goal-setting portal, and (5) personalised e-newsletters. The primary outcome was feasibility (recruitment, participation, and retention rate). Secondary outcomes were user engagement, acceptability, and changes in dietary intake and habits. Descriptive statistics were presented for the intervention and control groups. Generalised linear models estimated group differences in outcomes at 12-weeks. Results Of the 125 eligible individuals who registered Veg4Me accounts, 116 were randomised and 83 completed postintervention data collection. Recruitment, participation and retention rates were 47%, 93% and 72%, respectively. Intervention participants had higher engagement (median 20 [IQR 3, 54] vs. 6 [IQR 1, 28] page visits/week) and acceptability of the intervention (76%; vs. 52%) than control. Almost all intervention participants liked having access to the recipe library (93%) and reported that the e-newsletters prompted them to access the intervention (90%). Most accessed the goal-setting function (78%), food environment map (76%), and healthy eating resources (63%). More intervention participants reported their vegetable intake had changed in the last 12 weeks, compared with the control (85% vs. 57%; p = 0.010). Mean vegetable intake at 12 weeks for intervention and control was 2.73 (SD 1.1) and 2.66 (SD 1.4) serves/day, respectively (p = 0.76). At 12 weeks, for the intervention and control, confidence to shop regularly for nutritious foods was 68% and 55% (p = 0.09), to cook root vegetables was 88% and 81% (p = 0.11), and to cook pulses was 54% and 48%, respectively (p = 0.52). Conclusions A co-designed and personalised digital intervention to increase vegetable intake was feasible, engaging and acceptable among rural-dwelling young adults. Although change in reported vegetable intake was small, findings showed promise for improving dietary intake and habits. Larger trials of effectiveness are needed to determine whether personalised digital interventions can help address health inequities experienced by rural-dwelling young adults. Trial registration Australia New Zealand Clinical Trials Registry, ACTRN12623000179639, prospectively registered on 21/02/2023, according to the World Health Organizational Trial Registration Data Set. Universal Trial Number U1111-1284-9027.